2021
DOI: 10.3233/prm-200779
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric unilateral spatial neglect: A systematic review

Abstract: PURPOSE: Unilateral spatial neglect (USN), an inability to attend to one side of space or one’s body, is commonly reported in adult stroke survivors and is associated with poor outcomes. USN has been reported in pediatric survivors of stroke, but its impact is unclear. The purpose of this systematic review was to summarize and evaluate the literature regarding USN in pediatric stroke survivors. METHODS: PRISMA guidelines, Scopus, CINAHL, PubMed, and other relevant databases were searched with terms including “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Indeed, previous research showed that early brain injuries produce specific spatial cognitive deficits [205][206][207][208][209]. Unilateral brain damage in children with hemiplegic CP may disrupt the processing of visual information, resulting in unilateral spatial neglect manifested as an inability to attend, process, and report on sensory events occurring in one side of extrapersonal space [155][156][157]210,211]. For example, children with hemiplegic CP tend to draw asymmetrical pictures of the human body, often distorting the side of the picture corresponding to their own affected limb [153,212].…”
Section: Visuoperceptual and Spatial Neglectmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, previous research showed that early brain injuries produce specific spatial cognitive deficits [205][206][207][208][209]. Unilateral brain damage in children with hemiplegic CP may disrupt the processing of visual information, resulting in unilateral spatial neglect manifested as an inability to attend, process, and report on sensory events occurring in one side of extrapersonal space [155][156][157]210,211]. For example, children with hemiplegic CP tend to draw asymmetrical pictures of the human body, often distorting the side of the picture corresponding to their own affected limb [153,212].…”
Section: Visuoperceptual and Spatial Neglectmentioning
confidence: 99%
“…For example, children with hemiplegic CP tend to draw asymmetrical pictures of the human body, often distorting the side of the picture corresponding to their own affected limb [153,212]. Although spatial neglect in children with hemiplegic CP is often identified with paper-and-pencil tests, the latter might be less effective than functional assessments [211]. In general, the scarcity of quality research on spatial neglect in pediatric populations has resulted in the lack of valid assessment and treatment methods [211].…”
Section: Visuoperceptual and Spatial Neglectmentioning
confidence: 99%
See 1 more Smart Citation